Advanced Study on Improving the Noise of Mechanical Compressor Subjected to Repetitive Pressure Loading - Seong-woo Woo; Dennis L. O’Neal (Advanced Aspects of Engineering Research Vol. 2, 2021)
To improve the design of a new compressor system subjected to repetitive pressure loading, parametric Accelerated Life Testing (ALT) as new reliability methodology is suggested as a way to identify and reduce the fatigue failure due to design faults in the mechanical systems. The methodology includes: (1) a parametric ALT plan based on product BX lifetime, (2) load analysis, (3) a tailored sample of parametric ALTs with the design modifications and (4) an evaluation of whether the final design(s) of the product achieves the target BX lifetime. As a test case, a newly designed compressor in a French refrigerator was evaluated. The compressor was redesigned to improve its energy efficiency. However, the refrigerator models with this compressor made undesirable noises and vibrations in field. Consequently, consumers requested replacement of their refrigerators. When the sound level of the problematic refrigerators was recorded for vibration, the result was 0.35G in an anechoic chamber. Upon closer inspection of the refrigerator, the noise originated in the reciprocating compressor where there was interference between the compressor upper shell and the stator frame in the compressor. The compressor noise needed to be reproduced experimentally to evaluate any design flaws. After the mechanical pressure loads of the compressor were analyzed in a simple vapor-compression cycle, a parametric ALT was then performed. The failure shapes in the first ALT were similar to those of the failed products from the field. As a corrective action, the stator frame in the compressor system was reshaped to increase the minimum gap between the compressor upper shell and the stator frame. During the second ALT, there were no problems. After parameter ALTs with corrective action plans, the lifetime of the newly designed compressor was assured to have a B1 life 10 years with a failure rate of 0.1%/year.